The Effect of Intangible Assets on The Financial Performance, Financial Policy and Corporate Value of LQ 45 Companies Listed on The IDX in 2018-2022 - Bernadeta Longa; Riris Rotua Sitorus (CV. Syntax Corporation Indonesia, 2024)
This research was written with the aim to determine the effect of intangible assets on financial performance, financial policies, and firm value with assets size and leverage as control variables for LQ 45 companies in the period of 2018-2022. This type of research is a causal study that is based on cause and effect. The type of data used in this research is quantitative data in the form of intangible assets, assets size, leverage, financial performance, financial policies, and firm value. The data source for this research is the financial statements of companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, for a period of 5 years. The population in this research is LQ 45 companies listed on the IDX. The sample in this research is 18 companies multiplied. The sampling technique used in this study is non-probability sampling. The results of this research show that intangible assets have a positive effect on financial performance, financial policies, and firm value.